Analisis Enterprise Architecture Menggunakan COBIT 5 – APO03.01 dan APO03.02 - Diana Trivena Yulianti; Adelia Adelia; Giovanni Matthew Reynaldo (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Abstract — Enterprise architecture design in organizations is one way to find out the information technology used by organizations today, especially in PT. Manufaktur Rak Gondola. PT. Manufaktur Rak Gondola uses the TOGAF 9.1 framework in designing the organization's corporate architecture. Enterprise architecture management analysis aims to ensure that all components that support the process are running well, are identified and functioning properly. The analysis carried out at the same time as the enterprise architecture design process, it will improve the quality of the resulting enterprise architecture design. The results of the analysis can be used as recommendations for adequate control in the running process. The design process that has been carried out, was analyzed using COBIT 5, APO03.01, and APO03.02. The analysis was carried out to ensure compatibility of the TOGAF framework with the controls found in COBIT 5. Keywords— APO03.01, APO03.02, COBIT 5, Enterprise architecture, TOGAF 9.1